2012
DOI: 10.1155/2012/205752
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in Mitofusin-2 Gene with Type 2 Diabetes in Han Chinese

Abstract: MFN2 and ESRRA are candidate genes involved in the pathogenesis of T2D. Five tag-SNPs in MFN2 gene and three in ESRRA gene were selected and genotyped with TaqMan or PCR-RFLP method in stage 1 populations (555 patients with T2D and 649 control subjects) and stage 2 populations (546 patients with T2D versus 419 control subjects) in Han Chinese. And combining our published data, we estimated the interactions between genetic variants in the MFN2, ESRRA, and PGC-1α genes on the T2D risk using MDR. rs873458 (G > A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The MFN2 gene has been shown to be correlated with several liver diseases, including fatty liver and liver failure ( 8 ). Previous studies have shown that single-nucleotide polymorphisms (SNPs) in the MFN2 gene may regulate the function or expression of MFN2 and that over-expression of MFN2 reduces liver ischemia-reperfusion injury ( 9 , 10 ). Although studies have focused on the relationship between MFN2 gene polymorphisms and many diseases, such as essential hypertension ( 11 ) and axonal Charcot-Marie-Tooth disease (CMT2) ( 12 ), its correlation with ALF remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The MFN2 gene has been shown to be correlated with several liver diseases, including fatty liver and liver failure ( 8 ). Previous studies have shown that single-nucleotide polymorphisms (SNPs) in the MFN2 gene may regulate the function or expression of MFN2 and that over-expression of MFN2 reduces liver ischemia-reperfusion injury ( 9 , 10 ). Although studies have focused on the relationship between MFN2 gene polymorphisms and many diseases, such as essential hypertension ( 11 ) and axonal Charcot-Marie-Tooth disease (CMT2) ( 12 ), its correlation with ALF remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mfn2 deficiency also caused endoplasmic reticulum stress and mitochondrial dysfunction triggering reactive oxygen species, by which c‐Jun N‐terminal kinase was activated and led to insulin resistance. Importantly, type 2 diabetes mellitus was related to reduced expression of Mfn2, and SNPs of the MFN‐2 gene were reported to be associated with type 2 diabetes mellitus. The present study first identified that the A allele of rs1042842 in the MFN‐2 gene was significantly associated with GDM and increased 3‐h OGTT plasma glucose.…”
Section: Discussionmentioning
confidence: 52%
“…These were consistent with the results of previous study. According to traditional studies (29)(30)(31), functions of E2 were mainly mediated by receptors, including nuclear receptors (including ERa and ERb) and membrane receptor GPR30 (GPER-1). After binding with the receptor, E2 activated the transcription and translation of specific genes, and synthesized new functional proteins, thus producing biological effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ERa transcription factor was a key regulator of Mfn2 transcription (29). It has been found that a specific region of Mfn2 promoter could bind to and be activated by ERa (30). In addition, E2/GPER/ERK pathway could promote cell proliferation by up-regulating cyclinD1 (31).…”
Section: Discussionmentioning
confidence: 99%